EDUCATIONAL EQUITY AND LEARNING ENVIRONMENT OF SCHOOLS DIVISION OF ROXAS CITY - Besana, Michelle Ambion (President University, 2025)
Educational equity and learning environment are pressing issues among schools. Since the end of the COVID-19 pandemic, various programs monitoring efforts have been carried out to contribute significantly to the schools’ quality of services. One of those was this quantitative study which used a descriptive-correlational approach to investigate the level of educational equity and the extent of learning environment of junior high school students in Schools Division of Roxas City in the school year 2023-2024 as perceived by the teachers. After a comprehensive and critical review of data collected from two hundred and sixty-two (262) selected teacher-respondents, it was found that they perceived educational equity and learning environment as